IDADE DA FOLHA E RESISTÊNCIA DE VARIEDADES DE Brassica oleracea var. acephala A Brevicoryne brassicae (HEMIPTERA: APHIDAE) - Miranda, José Ednilson; Toscano, Luciana Cláudia; Bonacin, Gisèle Aparecida; Fernandes, Marcos Gino; Farias, Karine Freitas de (REVISTA DE AGRICULTURA, 2015)
IDADE DA FOLHA E RESISTÊNCIA DE VARIEDADES DE Brassica oleracea var. acephala A Brevicoryne brassicae (HEMIPTERA: APHIDAE)